Separation of isotopes of biogenic elements - Andreev, B. M. (Boris Mikhailovich) (Elsevier, 2007)
Separation of Isotopes of Biogenic Elements provides a detailed overview of this area of research covering all aspects from the value of isotope effects to their practical use (equilibrium single-stage isotope effect - kinetics and mass transfer multiplication of the single-stage isotope separation factor - technological peculiarity of processes) with the purpose of extraction from the natural mixture of the enriched and highly concentrated isotopes. In contrast to traditional books on the theory of isotope separation, the theoretical part of the book describes separation in two-phase processes in counter-flow columns. The experimental part of the book presents systematic analysis of specialists in the field of isotope separation in counter-flow columns. This book will be of interest to scientists, engineers and technical workers engaged in isotope separation processes and isotope application in nuclear physics, medicine, agro-chemistry, biology and other areas. This book may also be used in teaching theory and practical aspects in courses on physical chemistry and Isotope separation of light elements by physicochemical methods. * summarises current state of isotope research, especially biogenic elements * covering all aspects from the value of isotope effects to their practical use * of interest to scientists, engineers and technical workers engaged in isotope separation processes and isotope application.